2013
DOI: 10.2478/prolas-2013-0018
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Stone Fruit Viruses in Plum Orchards in Latvia

Abstract: Communicated by Edîte Kaufmane To evaluate the occurrence of nine viruses infecting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
5
7
0
Order By: Relevance
“…The results are in conjunction with (Brunt et al, 1996) who reported these stone fruits to be the hosts of PNRSV. Similar results have also been reported by a number of workers (Salam et al, 2007;Myrtra et al, 2003;Gospodaryk et al, 2013) who reported the presence of PNRSV at high concentration in different stone fruits.…”
Section: Host Range Studiessupporting
confidence: 80%
“…The results are in conjunction with (Brunt et al, 1996) who reported these stone fruits to be the hosts of PNRSV. Similar results have also been reported by a number of workers (Salam et al, 2007;Myrtra et al, 2003;Gospodaryk et al, 2013) who reported the presence of PNRSV at high concentration in different stone fruits.…”
Section: Host Range Studiessupporting
confidence: 80%
“…ACLSV belongs to the Flexiviridae family and Trichovirus genus (Martelli et al, 1994) and infects most plants of the Rosaceae family. It is more commonly found in pome fruits like apple and pear (Pupola et al 2011;Mazeikiene et al 2018) and less often in stone fruits -cherries, plums, apricots, peaches (Nemeth, 1986;Ulubas et al, 2004;Niu et al, 2012;Gospodaryk et al, 2013). ACLSV is easily spread through grafting and mechanical inoculation; there are no biological vectors.…”
Section: Introductionmentioning
confidence: 99%
“…The study demonstrated that stone fruit viruses are relatively not widespread in plum orchards in Latvia and that the commonly grown genotypes are infected with one or more of the tested viruses. In the future, the implementation of a programme to produce and propagate virus free planting material, along with the establishment of virus free planting material collections and certification programmes in the country, will play the key role for the containment of the spread of these viruses in the orchards (Gospodaryk et al, 2013).…”
Section: Main Plum Diseases In Latviamentioning
confidence: 99%